Luteolin–phospholipid complex: preparation, characterization and biological evaluation. (16th June 2014) - Khan, Junaid; Alexander, Amit; , Ajazuddin; Saraf, Swarnlata; Saraf, Shailendra
Abstract: Objectives: This study aims to develop novel carrier system incorporating luteolin, a poorly soluble biologically active plant active. Methods: We investigated a lipid-based drug delivery system to enhance dissolution and absorption profile of luteolin. Luteolin was complexed with phospholipids, and the preparation was characterized. The formulation was evaluated for physicochemical properties, in-vitro solubility or release studies. In vivo anti-inflammatory action of luteolin and its phospholipid complex was evaluated by using carrageenan and 12-O-tetradecanoylphorbol-13-acetate as inducers. Key findings: The prepared luteolin–phospholipid complex (LPC) showed drug loading of about 72.64% with average particle size of 152.6 nm. The Fourier transform infrared spectroscopy and thermal studies confirm formation of complex. The solubility of luteolin as LPC was about 2.5 times higher than the solubility of pure luteolin in water. In the diffusion study, LPC showed 95.12% of drug release at the end of 2 h. Animal studies demonstrated significant differences in response of LPC and luteolin. Conclusion: LPC was successfully prepared by optimizing the process parameters. The resultant delivery system improved bioavailability and efficacy of luteolin and in the future may become an efficient tool for administration of luteolin.